Effect of reverse twin-block and reverse pull mask face appliance for class III malocclusion on dento-facial morphology in Malay population - Fareen, Nashid (2018)
The treatment effect of Reverse Twin-Block and Reverse Pull Face Mask definitely produces some changes in the dento-facial structures, including the soft tissue. There is a lack of available literature in the management of Class III malocclusion as well as treatment effects of these particular appliances in Malay population. This crosssectional study was aimed to compare and analyse the craniofacial changes produced by Reverse Twin-Block and Reverse Pull Face Mask in early and late mixed dentition of Malay children having Class III malocclusion. Data consisted of pre- and post-treatment lateral cephalograms of 95 mixed dentition Malay children, 49 children treated by Reverse Twin-Block and 46 children treated by Reverse Pull Face Mask were divided into early (8-9years) and late (10-11years) mixed dentition groups. Treatment changes were assessed by Holdaway’s analysis, Ricketts analysis, Tweed’s analysis, pharyngeal airway space analysis and Steiner’s analysis using CASSOS and MITK software. Descriptive statistics and multiple linear regression were performed with the significance level set at 0.05. The result of the study revealed that the treatment effect of Reverse Twin-Block and Reverse Pull Face Mask has some statistically significant differences including gender disparities. However, these statistically significant changes were very minimum to notice clinically, except upper incisor proclination and upper lip protrusion. Reverse Pull Face Mask treated children had more proclined upper incisors and moreprotruded upper lip. The result also shows that different age group has no significant impact on the treatment effect. As, no significant differences were noted in treatment effects of early and late mixed dentition groups, the treatment of Class III malocclusion in Malay children can be delayed until late mixed dentition stage. It provides better patient compliance with less treatment time and cost. The treatment plan should be same for both male and female children, as the gender disparities found in the result were clinically unnoticeable. In conclusion, Reverse Pull Face Mask produced better treatment outcome with more proclined upper incisor and more protruded upper lip than Reverse Twin-Block in mixed dentition Malay children with Class III malocclusion.